2019
DOI: 10.1108/ijchm-10-2018-0876
|View full text |Cite
|
Sign up to set email alerts
|

Talent management meta review: a validity network schema approach

Abstract: Purpose The purpose of this paper is to critically assess the state of substantive, methodological and conceptual development of talent management (TM) within hospitality and business research and to identify gaps, examine debates and provide hospitality research direction. Design/methodology/approach After identifying 545 articles from 22 peer-reviewed journals from Google Scholar using “talent management,” only articles directly related to TM (n = 149) were analyzed using the validity network schema (VNS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 114 publications
2
36
2
2
Order By: Relevance
“…This is consistent with Taylor and Finley's (2010) suggestion that, in partnership with other colleagues, trainers can facilitate acculturation for temporary new employees. Management-on-training and talent management programs are also recommended to give interns a proper sense of responsibilities and make them better motivated (Self et al, 2019;D'Annunzio-Green, and Ramdhony, 2019;Murillo and King, 2019;Williamson and Harris, 2019;Shulga and Busser, 2019).. In addition, universities and vocational schools are recommended to prepare their students with skills that enable them to be better socialized.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This is consistent with Taylor and Finley's (2010) suggestion that, in partnership with other colleagues, trainers can facilitate acculturation for temporary new employees. Management-on-training and talent management programs are also recommended to give interns a proper sense of responsibilities and make them better motivated (Self et al, 2019;D'Annunzio-Green, and Ramdhony, 2019;Murillo and King, 2019;Williamson and Harris, 2019;Shulga and Busser, 2019).. In addition, universities and vocational schools are recommended to prepare their students with skills that enable them to be better socialized.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The importance of talent and its management is highlighted both for companies and for the academic field. There are numerous reports (Deloitte, 2015;BCG, 2018) contending that Talent Management (TM) in an organisational context is currently a priority issue for companies, as it can be a source of competitive advantages in their dynamic and competitive environments, providing strategic opportunities, and creating value (Lewis & Heckman, 2006;Collings & Mellahi, 2009, Farndale, Scullion & Sparrow, 2010Schuler, Jackson & Tarique, 2011;Meyers & van Woerkom, 2014;Makram, Sparrow & Greasley, 2017;Shulga & Busser, 2019;Sparrow, 2019). In the academic field, the relevance of talent and its management is also highlighted in literature reviews through bibliometric analyses carried out by Iles, Preece and Chuai (2010b), Gallardo-Gallardo, Nijs, Dries and Gallo (2015), Gallardo-Gallardo and Thunnissen (2016) and McDonnell, Collings, Mellahi and Schuler (2017), which provide increasing evidence of the popularity of the research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Further progress in the field of TM calls for studies on the following: (i) clarifying several aspects related to TM that are still imprecise (Thunnissen & Van Arensbergen, 2015;Gallardo-Gallardo & Thunnissen, 2016;Sparrow, 2019;Shulga & Busser, 2019), as despite abundant prior research on the definition of talent (Gallardo-Gallardo et al, 2013) and its operationalization (Nijs, Gallardo-Gallardo, Dries & Sels, 2014), there are still few studies on talent identification and location; (ii) the application of theoretical approaches such as the configurational one, which while arguably increasing the fragmentation of TM research (Sparrow, 2019) would also help to explain the process of identifying talent and grouping it into talent pools. Prior studies have already reported the existence of talent groupings (Björkman & Smale, 2010;Mäkelä, Björkman & Ehrnrooth, 2010), albeit without a theoretical grounding that explains the way of classifying these talented employees (Thunnissen & Gallardo-Gallardo, 2019), and (iii) new empirical evidence within a Spanish context, where prior research has indeed already been conducted (Vivas-López, Peris-Ortiz & Rueda-Armengot, 2011;Valverde, Scullion & Ryan, 2013;Vivas-López, 2014;Maqueira, Bruque & Uhrin, 2019), although there are only a handful of practical studies on how firms address the talent identification and grouping process.…”
Section: Introductionmentioning
confidence: 99%
“…This is also in accordance with Yildizayvaz, Akyol, and Demiral (2019), who assert that health workers, particularly nurses, play a central role in the management and administration of healthcare for patients. Moreover, in an era of health risks, HIV/AIDS epidemic, stressful work environment, and a turbulent environment to which health facilities such as hospitals are subjected, nurses are still required to provide essential services and tremendous support in peoples' lives (Andrioti et al 2017;Shulga and Busser 2019). At the same time, they consume a great deal of the country's resources economically (Hariyatia and Safrilb 2017;Nazir et al 2019).…”
Section: Introductionmentioning
confidence: 99%